2021
DOI: 10.3390/cancers13153835
|View full text |Cite
|
Sign up to set email alerts
|

A Multicentre Evaluation of Dosiomics Features Reproducibility, Stability and Sensitivity

Abstract: Dosiomics is a texture analysis method to produce dose features that encode the spatial 3D distribution of radiotherapy dose. Dosiomic studies, in a multicentre setting, require assessing the features’ stability to dose calculation settings and the features’ capability in distinguishing different dose distributions. Dose distributions were generated by eight Italian centres on a shared image dataset acquired on a dedicated phantom. Treatment planning protocols, in terms of planning target volume coverage and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 32 publications
(37 reference statements)
1
30
0
Order By: Relevance
“…Many studies have been performed on the stability of radiomic features, whereas only a few studies have reported on the stability of dosiomic features (6,7,22). This is the first report to introduce a concern about the stability of dosiomic features under interfractional error in radiation therapy.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Many studies have been performed on the stability of radiomic features, whereas only a few studies have reported on the stability of dosiomic features (6,7,22). This is the first report to introduce a concern about the stability of dosiomic features under interfractional error in radiation therapy.…”
Section: Discussionmentioning
confidence: 89%
“…, respectively. CV has been used in previous studies for radiomic feature stability analysis (19)(20)(21)(22). The CV was calculated for all features and all total numbers of fraction groups.…”
Section: Discussionmentioning
confidence: 99%
“…(b) Dosiomics is similarly subject to reproducibility issues because dose calculation algorithms, grid sizes, planners, and treatment regimens can lead to variations in DVI values and dosiomic characteristics. Recently, Placidi et al (168) evaluated the correlation between dosiomic properties and clinical outcomes by employing various dose calculation algorithms, 30 distinct dose distributions, and 2 grid resolutions at 8 centers to determine the sensitivity characteristics when there is a change in the dose distribution. This study favorably supports a multicenter investigation of this method, although only dosiomic signatures were considered, without including all possible RT techniques and excluding different feature extraction algorithms.…”
Section: Developments and Challenges In Dosiomicsmentioning
confidence: 99%
“…In the field of radiomics, the technology involved in the extraction of spatial information, which is used afterwards to construct prediction model, is named dosiomics. Through machine learning techniques, dosiomics extracts characteristics from 3D radiotherapy dose distribution by intensity, textural, and shape-based characteristics that allow a high complexity description of the dose distribution [ 97 , 98 ]. Dosiomics is increasingly used to improve the prediction of clinical outcomes and side effects, such as the locoregional recurrence in HNSCCs after intensity-modulated radiation therapy (IMRT) or local control after radiotherapy [ 99 ].…”
Section: Precision Medicine In Hnsccsmentioning
confidence: 99%